Perancangan Stiker Karakter Visual dalam Aplikasi Chatting: Kolaborasi Kebudayaan Jawa dan Wayang Kontemporer - Darmawan, Andreas James; Widyokusumo, Lintang; Puspitasari, Dyah Gayatri (Bina Nusantara University, 2015)
A new tradition in the use of chatting communication technology with mobile phone (cell phone) is more lively with the use of stickers. Stickers are used as a means to increase the emotion expressions of communication users. Current mobile phone technology, along with the development of high specifications (for visual depiction), is adequate to display complex visual. This prompts a new tradition that accepts even to be a new behavior in modern communication methods. Looking at this phenomenon, it is not impossible for an artist to open up the work area (creative economy) and the creation of new business areas in the visual characters of Indonesian culture. This study used the chatting phenomenon with stickers to introduce the culture of the puppet characters with contemporary approach for young people around the world. The method carried out included the depiction of classification of facial expression emotions and collaboration with the approach of some common sticker visualizations. The result was then put into the classification of semiotic theory combining with simplified visual approach to obtain the appropriate visual characterstics of the puppet. Research also involved visual craft of the purwa puppet as visual character basis for character deformation of the contemporary puppet. Thus, the application of visual stickers can be used by users for communication functions.